Corporate taxation and the impact of governance, political and economic factors - Marcel Gérard; Fernando M. M. Ruiz (Center for Economic Studies and ifo Institute (CESifo), 2009)
In this paper we first use two international data sets to investigate how governance, political and economic factors influence corporate tax rates. We show that institutional and political factors matter: good governance reduces the tax rate; a parliamentary system, especially a plurality election system, and religious or nationalist executives too, push tax rates upward. Traditional variables also matter: economic openness has a negative effect on tax rates although market size has a positive one. Though it is not robust, interaction among neighbors also plays a role. Then we turn to theory and extend a standard model of tax competition to provide a channel for the elements set forth so far to influence tax rates formation; nested in the economic theory of lobbying that exercise provides our empirical investigation with theoretical foundations.
Keywords: H73; H70; 330; institutions and taxation; tax competition; lobbying